A trajetória histórica da APAE: os casos de Getúlio Vargas e Passo Fundo RS, 1967-2008 - Soccol, Ingrid Pelissari Kravos (2019)
In the process of studying private institutions that provide services to people with disabilities, this research originated, which addresses the history of two entities from the Association of Parents and Friends of the Exceptional (APAE) of Getúlio Vargas - RS and Passo Fundo - LOL. For this, the history of the associations was researched and with a time frame that starts in the year of foundation of APAE Passo Fundo, in 1967 and ends in 2008, due to the National Policy of Special Education in the Perspective of Inclusive Education. It seeks to understand the legal changes that occurred between 1967 and 2008 and how these changes influenced the daily lives of people with disabilities. The sources used in the research include legal publications, documentation of the entities (book of minutes and photographic collection) and oral research carried out with people related to the APAEs of Getúlio Vargas - RS and Passo Fundo - RS, as family members of students, members of the board of directors , employees and former employees. This research took place in the perspective of regional history with an emphasis on the host cities of the associations. Through the study of regional history, we seek reflections of greater scope and the understanding of broader historical processes. Thus, it is understood that the study of the history of the proposed period is significant not only for the understanding of local history, but also enables the understanding of situations that involve the history of the education of the disabled at the national level, since it brings numerous elements that are representative of broader historical processes and contexts. In this context, we realize th at public assistance for the disabled began in the 1990s, covering investments at the federal, state and municipal levels, resulting in the consolidation of the institutionalization of special education, making these private associations socially constituted as the locus of disability and that educational issues about school inclusion are still being considered, discussed and organized by the responsible legal bodies.